Post‐CO2 injection alteration of the pore network and intrinsic permeability tensor for a Permo‐Triassic sandstone. Issue 2 (1st July 2015) - Hall, M. R.; Rigby, S. P.; Dim, P.; Bateman, K.; Mackintosh, S. J.; Rochelle, C. A.
Abstract: The aim of this study was to determine the process–structure–property relationships between the pre‐ and post‐CO2 injection pore network geometry and the intrinsic permeability tensor for samples of core from low‐permeability Lower Triassic Sherwood Sandstone, UK. Samples were characterised using SEM‐EDS, XRD, MIP, XRCT and a triaxial permeability cell both before and after a three‐month continuous‐flow experiment using acidic CO2 ‐rich saline fluid. The change in flow properties was compared to those predicted by pore‐scale numerical modelling using an implicit finite volume solution to the Navier–Stokes equations. Mass loss and increased secondary porosity appeared to occur primarily due to dissolution of intergranular cements and K‐feldspar grains, with some associated loss of clay, carbonate and mudstone clasts. This resulted in a bulk porosity increase from 18 to 25% and caused a reduction in mean diameter of mineral grains with an increase in apparent pore wall roughness, where the fractal dimension, D f, increased from 1.68 to 1.84. All significant dissolution mass loss occurred in pores above c . 100 μm mean diameter. Relative dilation of post‐treatment pore area appeared to increase in relation to initial pore area, suggesting that the rate of dissolution mass loss had a positive relationship with fluid flow velocity; that is, critical flow pathways are preferentially widened. Variation in packing density within sedimentary planes (occurring at cm‐scale along the ‐ z plane) caused the intrinsic permeability tensor to vary by more than a factor of ten. The bulk permeability tensor is anisotropic having almost equal value in ‐ z and ‐ y planes but with a 68% higher value in the ‐ x plane (parallel to sedimentary bedding planes) for the pretreated sample, reducing to only 30% higher for the post‐treated sample. The intrinsic permeability of the post‐treatment sample increased by one order of magnitude and showed very close agreement between the modelled and experimental results.